Athens connections associated with equipped distributions of three-composition distribution of athens space - Гребенюк, М. Ф. (Proceedings of National Aviation University (archive), 2021)
The differential geometry of multicomponent distributions of multidimensional spaces is considered. It is established that in the case of invariant normalization of the basic distribution, affine connections are determined internally by the three-component distribution in the main stratified variety. The components of the tensor of the curvature and torsion of these connections are found.